ISPD guidelines for peritoneal dialysis in acute kidney injury: 2020 Update (paediatrics). Issue 2 (March 2021) - Nourse, Peter; Cullis, Brett; Finkelstein, Fredrick; Numanoglu, Alp; Warady, Bradley; Antwi, Sampson; McCulloch, Mignon
Peritoneal dialysis (PD) for acute kidney injury (AKI) in children has a long track record and shows similar outcomes when compared to extracorporeal therapies. It is still used extensively in low resource settings as well as in some high resource regions especially in Europe. In these regions, there is particular interest in the use of PD for AKI in post cardiac surgery neonates and low birthweight neonates. Here, we present the update of the International Society for Peritoneal Dialysis guidelines for PD in AKI in paediatrics. These guidelines extensively review the available literature and present updated recommendations regarding peritoneal access, dialysis solutions and prescription of dialysis. Summary of recommendations: 1.1 Peritoneal dialysis is a suitable renal replacement therapy modality for treatment of acute kidney injury in children. (1C ) 2. Access and fluid delivery for acute PD in children. 2.1 We recommend a Tenckhoff catheter inserted by a surgeon in the operating theatre as the optimal choice for PD access. (1B ) (optimal ) 2.2 Insertion of a PD catheter with an insertion kit and using Seldinger technique is an acceptable alternative. (1C ) (optimal ) 2.3 Interventional radiological placement of PD catheters combining ultrasound and fluoroscopy is an acceptable alternative. (1D ) (optimal ) 2.4 Rigid catheters placed using a stylet should only be used when soft Seldinger catheters are not available, with the duration of use limited to <3 days to minimize the risk of complications. (1C ) (minimum standard ) 2.5 Improvised PD catheters should only be used when no standard PD access is available. (practice point ) (minimum standard ) 2.6 We recommend the use of prophylactic antibiotics prior to PD catheter insertion. (1B ) (optimal ) 2.7 A closed delivery system with a Y connection should be used. (1A ) (optimal ) A system utilizing buretrols to measure fill and drainage volumes should be used when performing manual PD in small children. (practice point ) (optimal ) 2.8 In resource limited settings, an open system with spiking of bags may be used; however, this should be designed to limit the number of potential sites for contamination and ensure precise measurement of fill and drainage volumes. (practice point ) (minimum standard ) 2.9 Automated peritoneal dialysis is suitable for the management of paediatric AKI, except in neonates for whom fill volumes are too small for currently available machines. (1D) 3. Peritoneal dialysis solutions for acute PD in children 3.1 The composition of the acute peritoneal dialysis solution should include dextrose in a concentration designed to achieve the target ultrafiltration. (practice point ) 3.2 Once potassium levels in the serum fall below 4 mmol/l, potassium should be added to dialysate using sterile technique. (practice point ) (optimal ) If no facilities exist to measure the serum potassium, consideration should be given for the empiric addition of potassium to the dialysis solution after 12 h of continuous PD to achieve a dialysate concentration of 3–4 mmol/l. (practice point ) (minimum standard ) 3.3 Serum concentrations of electrolytes should be measured 12 hourly for the first 24 h and daily once stable. (practice point ) (optimal ) In resource poor settings, sodium and potassium should be measured daily, if practical. (practice point ) (minimum standard ) 3.4 In the setting of hepatic dysfunction, hemodynamic instability and persistent/worsening metabolic acidosis, it is preferable to use bicarbonate containing solutions. (1D ) (optimal ) Where these solutions are not available, the use of lactate containing solutions is an alternative. (2D ) (minimum standard ) 3.5 Commercially prepared dialysis solutions should be used. (1C ) (optimal ) However, where resources do not permit this, locally prepared fluids may be used with careful observation of sterile preparation procedures and patient outcomes (e.g. rate of peritonitis). (1C ) (minimum standard ) 4. Prescription of acute PD in paediatric patients 4.1 The initial fill volume should be limited to 10–20 ml/kg to minimize the risk of dialysate leakage; a gradual increase in the volume to approximately 30–40 ml/kg (800–1100 ml/m 2 ) may occur as tolerated by the patient. (practice point ) 4.2 The initial exchange duration, including inflow, dwell and drain times, should generally be every 60–90 min; gradual prolongation of the dwell time can occur as fluid and solute removal targets are achieved. In neonates and small infants, the cycle duration may need to be reduced to achieve adequate ultrafiltration. (practice point ) 4.3 Close monitoring of total fluid intake and output is mandatory with a goal to achieve and maintain normotension and euvolemia. (1B ) 4.4 Acute PD should be continuous throughout the full 24-h period for the initial 1–3 days of therapy. (1C ) 4.5 Close monitoring of drug dosages and levels, where available, should be conducted when providing acute PD. (practice point ) 5. Continuous flow peritoneal dialysis (CFPD) 5.1 Continuous flow peritoneal dialysis can be considered as a PD treatment option when an increase in solute clearance and ultrafiltration is desired but cannot be achieved with standard acute PD. Therapy with this technique should be considered experimental since experience with the therapy is limited. (practice point) 5.2 Continuous flow peritoneal dialysis can be considered for dialysis therapy in children with AKI when the use of only very small fill volumes is preferred (e.g. children with high ventilator pressures). (practice point)